Peritonealkarzinose bei gastrointestinalen Malignomen = Peritoneal carcinomatosis of gastrointestinal origin - März, Loreen; Hofheinz, Ralf-Dieter; Piso, Pompiliu Ioan (Der Onkologe, 2016)
Peritoneal carcinomatosis is defined as the seeding of malignant cells in the peritoneum. In primary peritoneal carcinomatosis, the cancer cells originate from the peritoneum itself, whereas they spread from another solid tumor in secondary peritoneal carcinomatosis. Amongst tumors of gastrointestinal origin, metastases from colorectal cancer are the most common, although the incidence in gastric cancer (30 %) is higher. The best method for diagnosis is computer tomography of the abdomen (with intravenous, oral, and rectal administration of contrast agent). Systemic chemotherapy is significantly less effective in patients with peritoneal metastases than in patients with metastases in solid organs (e. g. liver). Carefully chosen patients can be treated with cytoreductive surgery (CRS) in combination with intraabdominally applied hyperthermic intraperitoneal chemotherapy (HIPEC). The prognosis is highly dependent on the histology of the primary tumor as well as the extent of peritoneal seeding; the life expectancy can be between a few months and several years.